ANALYSIS THE CONTENT APPROPRIATENESS ENGLISH TEXTBOOK FOR TENTH GRADE STUDENTS OF SENIOR HIGH SCHOOL BY PRIVATE PUBLISHER - Novitasari, Elda; Asi, Natalina; Luardini, Maria Arina (Journal Compound: Improving the Quality of English Education, 2019)
This research aim to describe the Content Appropriateness English Textbook For Tenth Grade Students of Senior High School by Private Publisher (Intan Pariwara) in the aspect content appropriateness. This research was descriptive qualitative with content analysis. The textbook was evaluated by using Krippendorf’s content analysis: unitizing, sampling, coding, reducing data, inferring contextual phenomena, and narrating the result. The instrument in the research was the researcher herself through reading the textbook repeatedly and thoroughly. This is also done under the instrument issued by Board of National Education Standard. The result of the research shows as follow: The completeness of materials in this textbook almost met completely according to KI and KD for tenth grade students of senior high school (90,9%). The materials in this textbook provided 10 materials in the three kind of texts both of functional text, interpersonal text and transactional text but 1 material left or not be fulfilled. The depth of materials was mostly grouped into depth category for the exposure in functional text (90%), inaccurate texts (18,7%), the materials in the textbook was up to date, but none of the texts or activities in the textbooks support vocational skills (0%).